Tinjauan Yuridis Putusan Pengadilan Agama Stabat No.1062/Pdt. G/2015/PA.Stab Tentang Pembatalan Hibah Perspektif Teori Keadilan - Hasibuan, Ahmad Soleh; Nasution, Nindi Aliska (Jurnal Ilmiah Global Education, 2024)
This study aims to analyze the decision of the Religious Court Stabat No.1062/Pdt. G/2015/PA.Stab regarding grant cancellation. This study uses a statutory and conceptual approach. The data sources used are primary data sources consisting of decisions from the Religious Courts, compilations of Islamic law, books of civil law laws, compilations of sharia economic laws. Meanwhile, secondary sources of law consist of books of Islamic jurisprudence, law books, and scientific journal articles. The results of this study indicate that the panel of judges examining cases of disputes over the cancellation of grants uses article 35 paragraph 1, article 36 paragraph 1 of law number 1 of 1974 concerning joint property and article 1338 of the Civil Code regarding agreements/agreement, thus ignoring the article regarding the permissibility of withdrawing a grant object even though the grant is without the approval of other heirs. The panel of judges should ideally be guided by the concept of Maqasid Syari'ah, namely maintenance of property and offspring. Thus, it can avoid negative impacts that will occur in family ties, such as the relationship between parents and their heirs. However, according to Hans Kelsen's theory of justice, the legal considerations made by judges in deciding cases of cancellation of grants are inconsistent in terms of the application of the legal system in force in Indonesia because according to him a sense of justice has not been fulfilled for justice seekers.